Implementing Arbitration Orders according to Jordan Legislations - Ali Melhem, Ayman Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
Study purpose :To negotiate Implementing Arbitration Orders in Jordan Arbitration Code , which is the most important element in arbitration judgments regarding to this implementation elements whether positive or negative , and the implementation parties with it’s mechanism to reach the result of the final arbitration order on Home Land.Through this study , it becomes clear to us that the implementation of arbitration order is the result that litigant aspired by the arbitration litigants which is the final purpose of arbitration parties . Arbitration process and implementing these orders are not be carried out but according to terms and conditions must be undertaken . And that there are problems that face arbitrators orders , and because we found that the national arbitration is under studying ; I try to mention implementing foreign arbitration order that other study dealt with which follows implementing executing orders of foreign courts , agreements and international treaties ; therefore there in no need to continue studying them .